Production of Glucose from Cassava Using Rice - Adebisi , Olosunde William; Okon , Antia Orua (Novel Aspects on Chemistry and Biochemistry Vol. 8, 2023)
Cassava and rice are abundantly readily available for use as appropriate in form(s) that may be desired; hence it is necessary to provide information on a novel approach that would support and boost the production of glucose syrup and other related products through the use of glucose produced using cassava starch as substrate and glucoamylase as enzyme sourced from rice. The enzymatic hydrolysis was carried out at optimum conditions of pH 5 and temperature under normal atmospheric pressure. The use of cassava starch from TMS 30572 cassava tuber variety in Nigeria revealed that enzyme (glucoamylase) sourced from rice could be utilized in hydrolysing the cassava starch to produce high yield of glucose that could possibly support the glucose syrup and other related industries. The production of glucose was found to be optimal at a specific reaction velocity of 0.00205 ± 0.00005\(\mathit{gDper}\) \(\mathit{litre-min}\) \(\mathit{per}\) \(\mathit{subtrate }\) \(\mathit{concentration}\) %\(\mathit{w}\)/\(\mathit{v}\). This value was reported to be close with the values obtained using model Equations 1 and 2.